Enhancing Urban and Rural Resilience to River Floods: Strategies From Pasar Kliwon and Mojolaban Districts - Pinta Rachmadani; Andri Kurniawan; Erlis Saputra (JPG (Jurnal Pendidikan Geografi), 2026)
Resilience is an important aspect in region development planning, particularly in facing disaster threats that are increasingly escalating due to climate change, such as river floods. However, it must be understood that differences in characteristics between regions can shape distinct resilience conditions. This study aims to formulate strategies for strengthening regional resilience against river floods by considering two different regional characteristics: urban in Pasar Kliwon District, Surakarta City, and rural in Mojolaban District, Sukoharjo Regency. A descriptive qualitative approach is used in this study. SWOT analysis is utilized to identify the internal and external conditions of the regions as well as to formulate strategies for strengthening resilience. Data collection was conducted through in-depth interviews with key informants selected using purposive sampling. Furthermore, the interview results were also supported by field observations and the analysis of planning documents in both regions. Based on the SWOT analysis, both urban and rural areas share similar strengths and external conditions, including high levels of community social capital, opportunities arising from spatial planning regulations, and common threats related to upstream flood risks. However, significant internal differences exist between the two areas. Urban areas benefit from relatively effective flood control infrastructure and stronger institutional capacity but are constrained by high settlement density and the degradation of tributary ecosystems. In contrast, rural areas are characterized by more natural environmental conditions, while facing limitations in flood control infrastructure, government budget capacity, fragile community economic resilience, and increased land-use change. Consequently, the strategy for strengthening urban resilience needs to focus on strengthening flood protection infrastructure, improving spatial planning and controlling land use in flood prone areas, and maintaining river ecosystems. Meanwhile, the strategy for strengthening rural resilience focuses more on implementation spatial planning based on flood risk reduction, developing collaboration with the private sector, and strengthening local economic capacity.